Layer-by-layer assemblies for drug delivery - Zapotoczny, Szczepan (Henry Stewart Talks, 2023)
Layer-by-Layer (LbL) deposition techniques, Drug delivery systems, Fabrications of multilayer films and capsules using the LbL approach, Capsules on a solid core template, Capsules with liquid oil cores, Encapsulation and releasing mechanisms, Nano-emulsions